POTENSI MEMBANGUN KEMITRAAN UNTUK PENINGKATAN PRODUK UNGGULAN DALAM RANGKA PEMBANGUNAN EKONOMI DESA (LOKUS PADA DESA MESSA, KECAMATAN TEON NILA SERUA, KABUPATEN MALUKU TENGAH) - Annisa Anissa; Nur Fitri Rahmawati (JAMBIS : Jurnal Administrasi Bisnis, 2022)
Featured Products have great potential increasing economic growth if managed properly and right. One of them is the Integrated Cattle Farm. This study has been a partnership between the Ministry of Village PDTT, New Business BUMDes, and beef cattle breeders in Messa Village. They have collaborated in increasing and developing potential in the farm of beef cattle production to increase the community’s economic income, especially beef cattle breeders. This study aims to the determine the potential for building partnerships, implementing partnerships, and resolving the hindrance or obstacle that arises in building partnerships. The method used is qualitative research by applying descriptive research and data analysis using data reduction, presentation, and conclusion. The study result show that this partnership relationship has been quite successful because it is beneficial for farmers to increase the family economy. This study shows that good and correct management in the developing superior products can significantly increase economic growth and income in building partnerships.